Style - Haynes, John, 1936- (Routledge, 1995)
Choosing le mot juste. Following and flouting conventions. Live and dead metaphors. Patterns of words in a text. Patterns of grammar in a text. The textual orchestration of patterns. The effects of the medium. Sequences of words and events. The selection of significant detail...